A novel ANO3 variant identified in a 53-year-old woman presenting with hyperkinetic dysarthria, blepharospasm, hyperkinesias, and complex motor tics. Issue 1 (December 2016) - Blackburn, Patrick; Zimmermann, Michael; Gass, Jennifer; Harris, Kimberly; Cousin, Margot; Boczek, Nicole; Ross, Owen; Klee, Eric; Brazis, Paul; Van Gerpen, Jay; Atwal, Paldeep
Abstract Background Cervical dystonias have a variable presentation and underlying etiology, but collectively represent the most common form of focal dystonia. There are a number of known genetic forms of dystonia (DYT1-27); however the heterogeneity of disease presentation does not always make it easy to categorize the disease by phenotype-genotype comparison. Case presentation In this report, we describe a 53-year-old female who presented initially with hand tremor following a total hip arthroplasty. The patient developed a mixed hyperkinetic disorder consisting of chorea, dystonia affecting the upper extremities, dysarthria, and blepharospasm. Whole exome sequencing of the patient revealed a novel heterozygous missense variant (Chr11(GRCh38): g.26525644C > G; NM_031418.2(ANO3): c.702C > G; NP_113606.2. p.C234W) in exon 7 in theANO3 gene. Conclusions ANO3 encodes anoctamin-3, a Ca+2 -dependent phospholipid scramblase expressed in striatal-neurons, that has been implicated in autosomal dominant craniocervical dystonia (Dystonia-24, DYT24, MIM# 615034). To date, only a handful of cases of DYT-24 have been described in the literature. The complex clinical presentation of the patient described includes hyperkinesias, complex motor movements, and vocal tics, which have not been reported in other patients with DYT24. This report highlights the utility of using clinical whole exome sequencing in patients with complex neurological phenotypes that would not normally fit a classical presentation of a defined genetic disease.